Bibliographic analysis of P53 gene family and gene expression analysis of P63 in Nasopharyngeal Carcinoma (NPC) - Thanes, Gunasekaran (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Nasopharyngeal Carcinoma (NPC) is one of the common diseases in Asia countries especially in Southern China. According to Malaysia National Cancer Registry (NCR) on the year 2002, its ranked NPC as the second and high rate of cases for males (8%) from all cancers for males in Malaysia. While for female it has been ranked as tenth cancer which was 2.8% of all cancer diagnosed by Malaysia females. Cancer has been proven to be associated directly or indirectly to gene. The Tumor protein gene p63 might lead to the occurrence of carcinogenesis as well. There are still lack of evidence of the NPC predisposition gene that will development the tumor growth. Previous research has been suggested that p63 gene have been involved in NPC development. In this study, gene expression analysis was conducted on p63 with normal epithelium cells and tumor cell where it suggested that p63 gene maybe a possible factor for NPC predispositions. Besides that, this study also focuses on bibliographic analysis to discover the research trend on p53 gene family in nasopharyngeal carcinoma and the institution that have been contributes to the research. In this study it concludes that p63 gene is not differential expression in both cell lines which are tumor cell (TW04) and normal cell (NP69) and for the bibliographic analysis the number of publications on p53 gene family in nasopharyngeal carcinoma have been recorded highest on the year 2014 while Central South University from China have been identified as the most contribute institution on this research.